Isu Pemekaran Wiayah sebagai Komoditas Politik dalam Masyarakat To Pulo di Kabupaten Selayar - Indriani, Dwi; Sudarmono, Sudarmono (JPP (Jurnal Politik Profetik), 2021)
The decentralization of a local government administration is expected to promote the socio-economic prosperity of its community. One of the opportunities that could be done is by establishing a new autonomous region through redistricting. By provoking the issue of redistricting, local elites bring this issue to be a political commodity to expand their political popularity and increase their electability. This article aims to 1) identify the factors behind the demands for the establishing a new autonomous region by redistricting certain islands of the Kepulauan Selayar Regency; 2) describe the role of elites in the effort to expand the Regency of Kepulauan Selayar; and 3) analyze the current dynamics regarding the issue of the territorial redistriction of the Kepulauan Selayar Regency. By using a qualitative approach, it was found that geographical circumstances, socio-economic inequality of local indigenous people and differences of cultural identity were the factors behind the demand of establishing a new autonomous territory. It is also found that local elites played a significant role behind the redistricting agenda for some reason, particularly to sustain their power and authority. Even though the new territory is unable to be established, the issue is remained articulate.